2020
DOI: 10.1101/2020.03.18.996843
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simulation of Ca2+oscillations in astrocytes mediated by amyloid beta in Alzheimer’s disease

Abstract: Disruptions of astrocyte Ca 2+ signaling is important in Alzheimer's disease (AD) with the unclear mechanism of amyloid beta peptide (A). We have modified our previous computational model of spontaneous Ca 2+ oscillations in astrocytes to investigate the effects of Aon intracellular Ca 2+ dynamics. The simulation results have shown consistence with the previous experiments. Acan increase the resting concentration of intracellular Ca 2+ and change the regime of Ca 2+ oscillations by activating L-type volta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…The effects of different values of Aβ on calcium concentrations for C c and P c without applying the induced/control signals stimulus is presented in Figure 4 . It can be seen from Figure 4 that the simulated results and trends are fully consistent with the studies reported by Gao et al ( 2020 ). It is observed that Aβ alters the membrane potential which in turn can enhance the regime of Ca 2+ oscillations and increase the stable state concentration of Ca 2+ .…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…The effects of different values of Aβ on calcium concentrations for C c and P c without applying the induced/control signals stimulus is presented in Figure 4 . It can be seen from Figure 4 that the simulated results and trends are fully consistent with the studies reported by Gao et al ( 2020 ). It is observed that Aβ alters the membrane potential which in turn can enhance the regime of Ca 2+ oscillations and increase the stable state concentration of Ca 2+ .…”
Section: Resultssupporting
confidence: 89%
“…By activating the L-type VGCCs and metabolic glutamate receptors, or by increasing ryanodine receptor sensitivity and Ca 2+ leakage, Aβ will increase the resting concentration of intracellular Ca 2+ and adjust the regime of Ca 2+ oscillations. The primary target of Aβ neurotoxicity is thought to be astrocytes (Gao et al, 2020 ). Astrocytes communicate with neurons and other brain cells in a functional way.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations